PENGARUH OCCUPANCY DAN PENYELENGGARAN WEDDING TERHADAP PENDAPATAN MAKANAN DAN MINUMAN DI THE ST REGIS BALI RESORT - Ni Nyoman Sueni (Majalah Ilmiah Widyacakra, 2018)
This study aims to determine the significant influence between occupancy and wedding arrangements both simultaneously and partially to the income of food and beverages at St. Regis Bali Resort. The data used in this research is income statement year 2014-2016, for further analyzed by using multiple correlation analysis, multiple linear regression analysis, determination analysis, simultant significant test (F statistic test) and partial significant test (T test statistic). Based on the calculation results, obtained correlation coefficient 0.844 which means there is a very strong relationship between occupancy and the implementation of wedding to food and beverage income. For Regersion Analysis shows the result of equation Y = 1.120.691.278,423+ 102.383.586,011X1 + 538.394.444,866X2. Determination analysis shows that simultaneously occupancy and the implementation of wedding influence 71.2% while the rest of 28.8% influenced by other factors not examined. The result of significance test of F-test and T-test showed significant influence either simultaneously or partially. It can be seen from the result of F count equal to 40,888 bigger than F-table equal to 2,92. Similarly, the result of t calculate occupancy of 7.440 and t-hitung wedding of 3.302, where the value of t-hitung each variable is greater than the t-table that is equal to 1.697.